Responsible use to responsible harm: illicit drug use and peer harm reduction in a darknet cryptomarket. (17th November 2017) - Bancroft, Angus
Abstract : Sale of illicit drugs through online 'cryptomarkets' is a notable innovation in the illicit drug market. Cryptomarkets present new ways of configuring risk and harm in relation to drug use. I examine the kinds of knowledge and discourses users employed to do this. I argue that the lay/expert divide that creates a hierarchy of knowledge around drug use and harms is increasingly undermined by the creation of knowledge communities by drug users who make drug use work effectively for them. I draw on the discussion forum of a now defunct English language focused cryptomarket, anonymised as 'Merkat', collected between 2015 and 2016. Typically, vendors in the major cryptomarkets are based in the USA, UK, China, the Netherlands and Australia. Buyers were mainly located in the USA, UK, Australia and Western Europe. I scraped the market forum threads and coded on emergent themes. I found that risk worked along four axes, cultural normalisation/pathologisation, chemical potency, legal/policy and market, each of which required a set of practices and orientations to manage successfully. Users indicated that they had adapted many harm reduction practices, while also promoting a 'responsible harm' orientation where they sought to own and take charge of harm. The support infrastructure drew on knowledge from drug users, vendors and interested professionals. I conclude that cryptomarkets can provide a community infrastructure that supports the exchange of drugs and configures them as risky but manageable objects.